REDESIGNING MADRASAH BOS FUNDS: TRANSITIONING FROM BUREAUCRATIC FINANCING TO OPTIMIZING DIRECT STUDENT IMPACT IN EAST ACEH REGENCY - Supardi Supardi (Jurnal Ikhtibar Nusantara, 2026)
This policy paper examines the anomaly in the management of School Operational Assistance (BOS) funds, which has lost its philosophical orientation as an instrument of human capital investment. Through a qualitative case study approach utilizing the 2026 Budget Details (POK) documents from 10 State Madrasahs in East Aceh Regency, the study reveals that institutions are trapped in a bureaucratic survival mode. Billions of rupiahs are held hostage by fixed costs such as non-academic honorariums, utilities, and official travel expenses. Consequently, the proportion of funding that directly impacts students' physical well-being and critical reasoning (Direct Student Impact) including medical supplies for school clinics (UKS), science laboratory facilities, and research mentorship (MYRES/KSM) is systematically marginalized. The SWOT quadrant analysis places this financial governance in a vulnerable defensive position. The absence of local protective regulations legitimizes such waste administratively, silently threatening fundamental rights and hindering the competitive edge of East Aceh's youth amidst the region's low higher education participation. Employing William Dunn's evaluative criteria, this study rejects normative audit approaches and recommends a rational yet highly equitable structural intervention: the issuance of a Circular Letter by the Head of the East Aceh Ministry of Religious Affairs regarding a Ring-Fencing Policy. This regulation locks a minimum threshold of 30% of the total BOS funds exclusively for student-centered programs. This policy is not merely an administrative correction, but a humanistic and corrective measure to eradicate quality disparities among madrasahs and return the fiscal sovereignty of education to its rightful owners: the students. Keywords: BOS Funds, Policy Analysis, Direct Student Impact, Ring-Fencing, Madrasah, East Aceh, Human Capital.